Pengaruh Internal dan Eksternal Perusahaan terhadap Nilai Perusahaan pada Perusahaan Properti dan Real Estate - Santi Duwi Nuryani; Anita Wijayanti; Endang Masitoh (Universitas Batanghari Jambi, 2021)
This study aims to test and analyze the influence of leverage, liquidity, inflation, and interest rates on the value of the company. Property and real estate companies listed on the Indonesia Stock Exchange in 2016-2019 as a population. Purposive sampling method for sampling and research is quantitative type. The data sources used secondary data are obtained from annual financial statements and analysis used multiple linear regressions. The results of research into external factors of the company namely inflation and interest rates influenced the increase in the value of the company. While the company's internal factors namely leverage and liquidity do not affect the increase in the value of the company.